Hubungan Kek dan Anemia Pada Ibu Hamil Dengan Kejadian Stunting di Wilayah Kerja Puskesmas Margasari Kabupaten Tapin - Ratu, Reni Puspita; Istiqomah, Istiqomah; Darsono, Putri Vidiasari; Kusvitasari, Hairiana (JURNAL BIDANG ILMU KESEHATAN, 2025)
Stunting is a growth and developmental disorder among children under five caused by chronic malnutrition, resulting in height being below the standard for their age. This condition may begin as early as the prenatal period, even before pregnancy occurs. Based on data from the Margasari Health Center (EPPGBM), the prevalence of stunting increased consecutively from 5.8% in 2021 to 11.1% in 2022, and 16.2% in 2023. This study aimed to analyze the correlation between Chronic Energy Deficiency (CED) and anemia in pregnant women and the incidence of stunting among toddlers in the Margasari Health Center working area, Tapin Regency. The study employed a quantitative method with an analytical retrospective design. The population consisted of pregnant women who had children aged 24–59 months, totaling 80 respondents selected through total sampling. Data were analyzed using the Chi-Square test. The results showed a significant relationship between CED in pregnant women and stunting incidence (p-value K1 = 0.043 and K4 = 0.033). Similarly, anemia in pregnant women was significantly associated with stunting (p-value K1 = 0.025 and K4 = 0.043). In conclusion, CED and anemia during pregnancy are important contributing factors to stunting in the working area of Margasari Health Center, Tapin Regency.